The English works of Thomas Hobbes of Malmesbury, Volume 02 (of 11) - Hobbes, Thomas, 1588-1679; Molesworth, William, Sir, 1810-1855 (Salt Lake City, UT : Project Gutenberg, 2024)
"The English Works of Thomas Hobbes of Malmesbury, Volume 02 (of 11)" by Hobbes is a philosophical treatise written in the early 19th century. This volume presents Hobbes' exploration of government, society, and the laws of nature, shedding light on the foundational principles of civil governance and natural rights. It aims to discuss the duties and rights of individuals within a societal framework, emphasizing the need for a social contract to maintain order and prevent conflict. The opening of this volume lays the groundwork for Hobbes' argument, asserting that the natural state of humanity is one of conflict and competition, which he terms a "war of all against all." He critiques the belief that humans are inherently social beings, suggesting instead that their interactions are primarily driven by self-interest and mutual fear. In this chaos, Hobbes argues, establishing a civil society through mutual agreements and a common authority is essential for the preservation of peace and the protection of individual rights. He sets forth a methodical exploration of the principles underlying human nature, justice, contracts, and the formation of governments, providing a clear framework for understanding the complexities of political organization and moral philosophy. (This is an automatically generated summary.)
Philosophical rudiments concerning government and society: Of liberty. Of dominion. Of religion.
Release date is 2024-06-24
Emmanuel Ackerman, KD Weeks and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Philosophy, English -- 17th century